2015
DOI: 10.4172/2155-952x.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Factor Associated to Bacterial Vaginosis in Non-pregnant Women of North Indian Population

Abstract: Bacterial vaginosis is currently the most prevalent cause of vaginal infection and vaginal discharge among the sexually active women. Bacterial vaginosis is a complex microbiological disease. Therefore, we aimed to determine the association of risk factors for bacterial vaginosis patients. In the prospective study, we enrolled a total of 300 nonpregnant women. One hundred and twenty six women were positive for bacterial vaginosis, confirmed by Amsel's criteria and Nugent's scoring. One hundred and seventy four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The diagnosis of BV is complicated by the lack of consensus over what is defined as BV, the natural variation of the VMB in women of different racial backgrounds and the elusive polymicrobial etiology of BV. Several risk factors have been identified in the pathogenesis of BV, such as age, socioeconomical status, antibiotic usage, sexual behavior and ethnicity (Brumley, 2012;Singh et al, 2015;Ranjit et al, 2018). Lactobacillus bacteria are traditionally linked with a healthy VMB, but L. iners may be more pathogen than friend.…”
Section: Factors Complicating the Diagnosis Of Bvmentioning
confidence: 99%
“…The diagnosis of BV is complicated by the lack of consensus over what is defined as BV, the natural variation of the VMB in women of different racial backgrounds and the elusive polymicrobial etiology of BV. Several risk factors have been identified in the pathogenesis of BV, such as age, socioeconomical status, antibiotic usage, sexual behavior and ethnicity (Brumley, 2012;Singh et al, 2015;Ranjit et al, 2018). Lactobacillus bacteria are traditionally linked with a healthy VMB, but L. iners may be more pathogen than friend.…”
Section: Factors Complicating the Diagnosis Of Bvmentioning
confidence: 99%
“…Prior studies also proposes the role of vaginal douching in increasing the risk of BV and reccurent BV in non-pregnant females. 10,11,25,26 Our Findings stated that BV patient have a history of vaginal douching (34.3%). Research by Ranjit et al showed that 32.1% of BV patients (p=0.015) had a frequent vaginal douching habit compared with those who performed it occasionally.…”
Section: Discussionmentioning
confidence: 65%
“…11 Different research by Om et al and Bitew et al also suggest that vagina douching is increasing BV risk (OR=1.33: 95% CI 0.8 to 2.0) and (OR=1.73: 95% CI 0.99 to 3.04), respectively. 10,26 Vaginal douching can affect the ecosystem of vaginal microbiome, possibly promoting the growth of opportunistic pathogen bacteria. Discontinuation of vaginal douching is believed to reduce the risk of BV recurrence.…”
Section: Discussionmentioning
confidence: 99%